Influence of hybrid working arrangements on employee productivity in the Communications Authority of Kenya - Muriithi, L. M. (Strathmore University, 2023)
Hybrid working arrangements, which combine physical and remote work, have become more prevalent in the global economy and during the Covid-19 pandemic. However, the effects of these arrangements on employee productivity could be clearer. This study examined how hybrid working arrangements influenced employees’ productivity in the Communications Authority of Kenya (CA), a public entity regulating the communications sector. The study focused on four factors: human resource planning, ICT adoption, worklife balance, and work design. The study adopted a positivist research philosophy and utilized the descriptive and correlative research design. It used stratified sampling technique to select 153 respondents from a population of 248 CA employees across 20 departments. The data were collected through online and offline questionnaires and analysed using correlation and multiple regression analysis at a 0.05 significance level. The results strongly suggested that all four factors had positive and significant relationships with employee productivity. The study concluded that hybrid working arrangements could enhance employee productivity if supported by effective human resource planning, ICT adoption, work-life balance, and work design. The study recommended that CA develops and documents clear guidelines and standard operating procedures for hybrid working arrangements, adopts ICT in managing employees and workflow, observes appropriate deployment and working shifts, and adopts flexible work designs. The study was limited by its focus on one entity with advanced systems and its use of quantitative analysis only. Further research can be done on larger public corporations using qualitative methods to explore the underlying reasons for the findings.
Full- text thesis